ANALISIS PENERAPAN AKAD MUDHARABAH DAN WADI’AH DALAM PRODUK HAJJ BUSINESS DI CIMB NIAGA SYARIAH SURABAYA - Alfayed, Valke; Vahlevi, Dewi Riza Lisvi (Universitas Muhammadiyah Palembang, 2024)
Purpose– Sales Representatives play a vital role in the sales of Hajj Business products at CIMB Niaga Syariah. Their duties include promoting the products, explaining them to potential customers, and ensuring compliance with mudharabah and wadiah contracts throughout the sales process. Understanding how well Sales Representatives comprehend and apply these contracts in their sales practices is crucial for maintaining the integrity and success of Hajj Business products. Design/methodology– This study employs a qualitative approach using a case study method. Primary data was obtained through direct observation and documentation of the sales process conducted by the sales team. Three data collection techniques were used: observation, case studies, and documentation, to gain a comprehensive and in-depth understanding of the Hajj package sales process. Findings - The findings indicate that one key factor contributing to the stability of Hajj investments is the well-planned and meticulous management of funds. this study emphasizes the significant role of Sales Representatives in promoting and selling Hajj Business products and ensuring adherence to mudharabah and wadiah contracts at every stage of the sales process.